O portal público do Detran/PR como instrumento de exercício de cidadania - Dilly, Marcel (2009)
Electronic government (e-gov) is a new term that is becoming more and more present in the agenda of governments and the lives of citizens. By means of a virtual presence in the web, governments can now provide services and interact with people. This study had the main purpose of understanding the role of a government website as a tool to enhance citizenship. A quantitative approach was used, which involved the collection and analysis of data from a survey with users and non users of Detran/PR’s (Transit Authority) website. Additionaly to that, an interview was carried out with the manager in charge of the services and information provided in the website, which was more qualitative. Results show that the number of non users is relatively high, as expected. Although a huge range of services is provided on-line, many peple prefer to go to physically visit the store to solve their issues, or they are not suitably “digitally included” to consider the electronic service as an alternative. Among those who use Detran/PR’s website, one notices that they are pleased with the services that are provided and have a reasonable level of interest in interacting and contributing to the improvement of the services.